Changes in the growth and Lancemaside A content of Codonopsis lanceolata (deodeok) sprouts under LED-based lighting at different red/far-red ratios - Kim, Ye Lin; Sim, Han-Sol; Jang, Seong-Nam; Lee, Jin-Hui; Son, Ki-Ho (Frontiers in Plant Science, 2025)
IntroductionCodonopsis lanceolata (deodeok) is used in traditional medicine because it contains saponins with high medicinal value. While previous studies have explored the general effects of red/far-red (R/FR) ratios on plant morphology and secondary metabolites, the specific impact of FR light on plant growth and bioactive compound accumulation of C. lanceolata sprouts remains largely unexplored.MethodsHere, we established a cultivation method for the C. lanceolata short-cycle sprout form on a vertical farm. Plants were grown under four different R/FR light conditions: white light (control), R/FR 3.0, R/FR 1.2, and R/FR 0.75. All treatments were provided with the same PPFD (210 ± 10 μmol m⁻² s⁻¹), and FR light was added to adjust the R/FR ratio. This setup was used to investigate the effects of varying R/FR ratios on plant growth and changes in bioactive compound accumulation.ResultsFR supplementation significantly affected plant growth, development, and bioactive compound accumulation. Most growth parameters significantly increased as the R/FR ratio decreased. Adding FR light effectively increased the fresh and dry weight, plant height, leaf area, and node number. Moreover, the total phenolic content, flavonoid levels, and antioxidant capacity significantly increased at R/FR ratios of 1.2 and 0.75. The Lancemaside A content per plant was higher under FR supplementation than under white light treatment, slightly reducing at an R/FR ratio of 0.75 compared with that at 1.2, suggesting a possible inhibitory effect of excessive FR light.ConclusionsThe findings indicate that appropriate FR light supplementation can enhance biomass and increase bioactive compounds. Thus, FR supplementation in a vertical farming system could boost the growth and bioactive substance content of sprouts, which has potential value for pharmaceutical and cosmetic applications.